2018
DOI: 10.1038/s41598-018-21750-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous localisation of membrane proteins in Staphylococcus aureus

Abstract: The bacterial cytoplasmic membrane is the interface between the cell and its environment, with multiple membrane proteins serving its many functions. However, how these proteins are organised to permit optimal physiological processes is largely unknown. Based on our initial findings that 2 phospholipid biosynthetic enzymes (PlsY and CdsA) localise heterogeneously in the membrane of the bacterium Staphylococcus aureus, we have analysed the localisation of other key membrane proteins. A range of protein fusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…9B). Recent notable studies have demonstrated heterogeneous supramolecular localization of membrane proteins generally and at septa of Sau cells, including interacting enzymes that catalyze phospholipid biosynthesis and the MreD regulator of PG synthesis (56,57). This heterogenous localization results in punctate patterns of these proteins at division septa, resembling the localization of Spn PBPs reported here (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…9B). Recent notable studies have demonstrated heterogeneous supramolecular localization of membrane proteins generally and at septa of Sau cells, including interacting enzymes that catalyze phospholipid biosynthesis and the MreD regulator of PG synthesis (56,57). This heterogenous localization results in punctate patterns of these proteins at division septa, resembling the localization of Spn PBPs reported here (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…2 and S2). Polytopic MreD plays a role in supramolecular localization of the phospholipid biosynthesis enzymes, and heterogeneous punctate patterns are lost upon protein overexpression (57). A favored explanation for punctate supramolecular organization is that membrane protein complexes distort local curvature on membranes and thereby perturb diffusion, resulting in distribution patterns for the majority of membrane proteins (57).…”
Section: Discussionmentioning
confidence: 99%
“…To quantify this observation, we calculated the coefficient of variation (CV) of nuclear UHRF1-GFP among wt, Dppa3KO, and T12CM ESCs. The CV of a fluorescent signal correlates with its distribution, with low CV values reflecting more homogenous distributions and high CV values corresponding to more heterogeneous distributions 86,87 . Indeed, the pronounced focal accumulation of UHRF1-GFP observed in Dppa3KO and T12CM ESCs corresponded with a highly significant increase in the CV values of nuclear UHRF1-GFP compared with wt ESCs ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 Hz). Laser-based SRRF microscopy of conventional fluorophores has also been demonstrated in fixed bacteria for multi-colour imaging in B. subtilis ( Vega-Cabrera et al, 2017 ) and z-stack imaging of membrane proteins in S. aureus ( Weihs et al, 2018 ).…”
Section: Application Of Srrf Analysis In Different Microscopesmentioning
confidence: 99%